On Geometrical Properties of Some Banach Spaces - Simsek, Necip; Savas, Ekrem; Karakaya, Vatan (NATURAL SCIENCES PUBLISHING CORP-NSP, 2013)
In this work, we prove that modular spaces V rho(lambda; p) defined in [26] have the k-nearly uniform convexity(k - NUC property) when they are endowed with the Luxemburg norm. We also prove that these spaces have the uniform Opial property with the Luxemburg norm. The above investigated geometric properties will enable us to obtain some fixed point results in modular spaces.
Keywords: de la Vallee-Poussin means; Luxemburg norm; the uniform Opial property; k-nearly uniform convexity; SEQUENCE-SPACES; LA VALLEE; L(P); Mathematics; Physics